CLINICAL AND LABORATORY CHANGES IN HBV/HDV CO-INFECTION: PATHOPHYSIOLOGICAL AND CLINICAL INSIGHTS - Tolibjonova Malika Khusanovna; Oripov Nuriddin Najmiddinovich (Web of Journals Publishing, 2025)
Chronic hepatitis is a prolonged inflammatory liver disease, primarily caused by viral infections (HBV, HCV), autoimmune reactions, or toxic exposures. The chronic inflammatory process may result in hepatocyte injury, fibrosis, and cirrhosis, which determine the severity of the disease and the risk of complications.